The genus Cyperus (Cyperaceae) in the restinga of Pará state, Brazil - Conde, Maíra Luciana Guimarães; Nunes, Clebiana de Sá; Gil, André dos Santos Bragança (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2022)
This work presents a taxonomic treatment of Cyperus sensu lato species in restingas in the state of Pará, Brazil. The collections of the MG, IAN, and HBRA herbaria were examined, collections were made between May and June 2017, and 16 species of Cyperus s.l. were determined. A taxonomic identification key, descriptions, geographic distribution, illustrations, and taxonomic comments of each species found are presented.